Ask the Dreams: A Cosmopolitics of Native Peoples for the Meaning of Life - Tasso, Luciano (Revista do Colóquio, 2025)
This work was constructed based on research conducted for the Seminar of Advanced Studies in Art and Culture, offered by the Postgraduate Program in Arts of the Federal University of Espírito Santo (UFES); its central theme is symbolic processes that shape the formation of thought and their implications for the construction of the future. For this purpose, we brought together ideas from Ailton Krenak and Roque Laraia, in order to reflect on how cosmogonic alternatives of indigenous peoples can change our worldview and stimulate artistic productions committed to challenging concepts inherited from hegemonic cultures.